The Nucleoprotein and Phosphoprotein of Measles Virus - Guseva, Serafima; Milles, Sigrid; Blackledge, Martin; Ruigrok, Rob W. H. (Frontiers in Microbiology, 2019)
Measles virus is a negative strand virus and the genomic and antigenomic RNA binds to the nucleoprotein (N), assembling into a helical nucleocapsid. The polymerase complex comprises two proteins, the Large protein (L), that both polymerizes RNA and caps the mRNA, and the phosphoprotein (P) that co-locallises with L on the nucleocapsid. This review presents recent results about N and P, in particular concerning their intrinsically disordered domains. N is a protein of 525 residues with a 120 amino acid disordered C-terminal domain, Ntail. The first 50 residues of Ntail extricate the disordered chain from the nucleocapsid, thereby loosening the otherwise rigid structure, and the C-terminus contains a linear motif that binds P. Recent results show how the 5’ end of the viral RNA binds to N within the nucleocapsid and also show that the bases at the 3’ end of the RNA are rather accessible to the viral polymerase. P is a tetramer and most of the protein is disordered; comprising 507 residues of which around 380 are disordered. The first 37 residues of P bind N, chaperoning against non-specific interaction with cellular RNA, while a second interaction site, around residue 200 also binds N. In addition, there is another interaction between C-terminal domain of P (XD) and Ntail. These results allow us to propose a new model of how the polymerase binds to the nucleocapsid and suggests a mechanism for initiation of transcription.